Intermediate leader: Influence on the Transformation of Pedagogical Leadership Practices of School Officers - Chaucono Catrinao, Juan Carlos (2022)
The objective of the article is to expose and contextualize the experience developed by the intermediate leader in the transformation of the pedagogical leadership practices of school directors in the region of La Araucanía, Chile. This work subscribes to a case study that uses a qualitative methodology of a descriptive nature. In total, 6 professionals participated, 3 school directors and 3 heads of the Technical Pedagogical Unit. Regarding the development of this study, it was divided into three phases: 1) questioning for the discussion of critical knots, 2) accompaniment of the learning path to transform pedagogical leadership practices, and 3) critical reflection and professional challenges. The results indicate that the intermediate leader positively influenced the ways of leading the teacher's professional development and student learning, especially when systematic spaces for questioning reflection and in situ improvement on the practice of pedagogical leadership are promoted collaboratively. In conclusion, developing intermediate leadership practices from learning together and making shared decisions from real problems of pedagogical leadership favors the influence on the transformations of pedagogical leadership practices.